2020
DOI: 10.1007/s00520-020-05601-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidental pulmonary embolism in oncologic patients—a systematic review and meta-analysis

Abstract: Purpose Incidental pulmonary embolism (IPE) is a common finding on computed tomography (CT). IPE is frequent in oncologic patients undergoing staging CT. The aim of this analysis was to provide the pooled frequency of IPE and frequencies of IPE in different primary tumors. Methods MEDLINE, SCOPUS, and EMBASE databases were screened for studies investigating frequency of IPE in oncologic staging CT up to February 2020. Overall, 12 studies met the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
(49 reference statements)
2
20
0
Order By: Relevance
“…According to another study by Ohashi et al ( 13 ), the most common type of cancer associated with the occurrence of PE was pancreatic cancer and the majority of the patients were at an advanced stage when diagnosed with PE. Furthermore, Meyer et al ( 14 ), in their study on cancer patients with PE, found that 3,36% had asymptomatic PE. The most common type of cancer was prostate cancer, followed by hepatobiliary carcinoma and pancreatic cancer ( 14 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to another study by Ohashi et al ( 13 ), the most common type of cancer associated with the occurrence of PE was pancreatic cancer and the majority of the patients were at an advanced stage when diagnosed with PE. Furthermore, Meyer et al ( 14 ), in their study on cancer patients with PE, found that 3,36% had asymptomatic PE. The most common type of cancer was prostate cancer, followed by hepatobiliary carcinoma and pancreatic cancer ( 14 ).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, Meyer et al ( 14 ), in their study on cancer patients with PE, found that 3,36% had asymptomatic PE. The most common type of cancer was prostate cancer, followed by hepatobiliary carcinoma and pancreatic cancer ( 14 ). In another study by Silva et al ( 4 ), it was found that the majority of the cancer patients who developed PE were female and the most common types of cancer were colorectal and lung cancer, most of which had metastases or had received chemotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…With the improved image resolution and frequent use of multi‐detector CT scanners, 4 the prevalence of incidental VTE has increased. A recent large meta‐analysis showed that the overall frequency of incidental pulmonary embolism (PE) was 3.36% in oncology patients 5 . Several studies have evaluated the prognosis and the clinical course of incidental VTE in the cancer population, but the optimal management of these patients is still debated.…”
Section: Introductionmentioning
confidence: 99%
“…A recent large meta-analysis showed that the overall frequency of incidental pulmonary embolism (PE) was 3.36% in oncology patients. 5 Several studies have evaluated the prognosis and the clinical course of incidental VTE in the cancer population, but the optimal management of these patients is still debated. Current international guidelines recommend the same management for both clinically suspected and incidentally detected cancer-associated VTE, 6,7 but the supporting evidence is limited to mostly observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…The increased use of CT scans in cancer patients and the introduction of multiple-detector CT scanners with their imaging quality that evolved over recent years have increased the incidence of incidental cancer-associated PE. In a recent systematic review and meta-analysis including 28 626 patients, the prevalence of incidental PE in cancer patients was 3.4% (95% confidence interval [CI], 3.2%-3.6%), with the lowest frequency observed in tumors of male reproductive organs (0.8%, 95% CI, 0.2%-1.4%) and the highest observed in patients with prostate cancer (8.6%, 95% CI 3.7%-13.4%) [5]. Several studies have evaluated the prognosis and the clinical course of incidental VTE in the cancer population, but the optimal management of these patients is still debated.…”
Section: Introductionmentioning
confidence: 99%